Antioxidant effects of nanoencapsulated lipoic acid in tissues and on the immune condition in haemolymph of Pacific white shrimp Litopenaeus vannamei (Boone, 1931). (22nd January 2018) - da Silva Martins, Á.C.; Artigas Flores, J.; Porto, C.; Romano, L.A.; Wasielesky Junior, W.; Caldas, S.S.; Primel, E.G.; Külkamp‐Guerreiro, I.; Monserrat, J.M.
Abstract: The antioxidant and oxidative damage responses and immune parameters in shrimp, Litopenaeus vannamei, reared in clear water (CW) and in a biofloc system (BFT) were evaluated. The animals were given feed supplemented with either nanocapsules containing the antioxidant lipoic acid (NCLA) or empty nanocapsules (NC). Antioxidant and oxidative stress analyses were evaluated by measuring glutathione S‐transferase activity (GST), reduced glutathione (GSH) concentration and lipid peroxidation (TBARS) in the gills, hepatopancreas and muscle. The immune parameters were then determined by the differential hemocyte count in the haemolymph. The final weight of the shrimp reared in both CW and BFT and treated with NCLA increased ( p < .05). The shrimps reared in BFT showed increased GST activity in the gills and hepatopancreas after NCLA treatment ( p < .05). Higher GSH levels were observed in the hepatopancreas with NCLA supplementation in CW and BFT ( p < .05). Decreased levels of TBARS were observed in the gills and muscles of shrimp supplemented with NCLA and maintained in CW ( p < .05). A decrease in the percentage of hyaline hemocytes and an increase in granular hemocytes were observed in shrimp treated with NCLA in CW and BFT ( p < .05). The antioxidant treatment induced positive responses in terms of the zootechnical, biochemical and immunological parameters.